Enhancement of the Listeria monocytogenes p60-specific CD4 and CD8 T cell memory by nonpathogenic Listeria innocua - Geginat, Gernot; Nichterlein, Thomas; Kretschmar, Marianne; Schenk, Simone; Hof, Herbert; Lalic-Mülthaler, Mio; Goebel, Werner; Bubert, Andreas (The journal of immunology, 1999)
The contact of T cells to cross-reactive antigenic determinants expressed by nonpathogenic environmental micro-organisms may contribute to the induction or maintenance of T cell memory. This hypothesis was evaluated in the model of murine Listeria monocytogenes infection. The influence of nonpathogenic L. innocua on the L. monocytogenes p60-specific T cell response was analyzed. We show that some CD4 T cell clones raised against purified p60 from L. monocytogenes cross-react with p60 purified from L. innocua. The L. monocytogenes p60-specific CD4 T cell clone 1A recognized the corresponding L. innocua p60 peptide QAAKPAPAPSTN, which differs only in the first amino acid residue. In vitro experiments revealed that after L. monocytogenes infection of APCs, MHC class I-restricted presentation of p60 occurs, while MHC class II-restricted p60 presentation is inhibited. L. innocua-infected cells presented p60 more weakly but equally well in the context of both MHC class I and MHC class II. In contrast to these in vitro experiments the infection of mice with L. monocytogenes induced a strong p60-specific CD4 and CD8 T cell response, while L. innocua infection failed to induce p60-specific T cells. L. innocua booster infection, however, expanded p60-specific memory T cells induced by previous L. monocytogenes infection. In conclusion, these findings suggest that infection with a frequently occurring environmental bacterium such as L. innocua, which is nonpathogenic and not adapted to intracellular replication, can contribute to the maintenance of memory T cells specific for a related intracellular pathogen.